La llama llama rojo pijama - Dewdney, Anna; Canetti, Yanitzia, 1967- (New York, N.Y. : Viking, 2011)
At bedtime, a little llama worries after his mother puts him to bed and goes downstairs.
Translation of: Llama, llama red pajama.
A partir de 2 años.
Accelerated Reader
Keywords: Mother and child -- Juvenile fiction; Bedtime -- Juvenile fiction; Llamas -- Juvenile fiction; Madre e hijo -- Novela juvenil; Hora de acostarse -- Novela juvenil; Llamas -- Novela juvenil